PENGARUH LOCUS OF CONTROL TERHADAP KESIAPAN SISWA KELAS XI ADMINISTRASI PERKANTORAN TAHUN AJARAN 2014/2015 SMK ADHIKAWACANA SURABAYA DALAM MENGHADAPI UJI KOMPETENSI KEAHLIAN - MARGARETA ORTLOFF, FARAH (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2015)
ABSTRACT One of the measurement to assess the student's level of competence in the field of his expertise as well as student performances that include aspects of knowledge, skills and attitudes of students of vocational high schools, then implemented Competency Skills Test.  Competency skill test needs readiness of students, one of which is the character's psychological character owned by students i.e. locus of control (LoC). This research aims to know the effect of locus of control on the readiness of grade XI Office Administration 2014/2015 academic year SMK Adhikawacana Surabaya, to facing the competency skills test. The type of this research is a descriptive quantitative approach. The sampling techniques using Proportional Random Sampling with 58 students as a sample. The collection of data method obtained with direct observation and documentation in the field. The analysis of the data used in this study is a simple linear regression analysis. From the results of this research show that there is a significant and positive effect among variables locus of control on the readiness of grade XI Office Administration SMK Adhikawacana Surabaya to facing the competency skill test. This is apparent from the value R Square of 57% with the regression coefficient is positive of 0,527 which suggests that locus of control have enough effect on the readiness of the grade XI Office Administration SMK Adhikawacana Surabaya in the face of the competency skill test. The rest amounted to 43% readiness of students influenced by factors other than the factor of locus of control.   Keywords : Locus of Control, the readiness of Student